Fibrous structure, and method for producing fibrous structure

The fiber structure, featuring polyester fibers with carboxy groups and cellulose fibers treated with specific hydrophilic agents, addresses the limitations of moisture absorption and texture in existing polyester fiber structures, achieving enhanced performance in moisture handling and dirt removal.

JP2025038697APending Publication Date: 2025-03-19KOMATSU SEIREN CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023145460
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-07
Publication Date
2025-03-19

AI Technical Summary

Technical Problem

Existing polyester fiber structures have limited moisture absorption and release properties, leading to a hard texture and reduced ease of dirt removal during washing, especially when combined with cellulose fibers.

Method used

A fiber structure comprising polyester fibers with carboxy groups and cellulose fibers, treated with a polymer of polyalkylene glycol diacryl ester and anionic hydrophilic agents, which are attached to the fiber surface to enhance moisture absorption and release properties while maintaining a soft texture.

Benefits of technology

The fiber structure achieves excellent moisture absorption and release properties, along with improved dirt removal efficiency and a soft texture, by balancing hydrophilicity and hydrophobicity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025038697000001_ABST
    Figure 2025038697000001_ABST
Patent Text Reader

Abstract

To provide a soft-feeling fibrous structure having excellent moisture absorption and desorption properties and SR performance, and a method for producing the fibrous structure.SOLUTION: Provided is a fibrous structure comprising polyester fibers having a carboxyl group in the molecular chain and cellulosic fibers, wherein the fiber surface carries with (A) a polymer of polyalkylene glycol diacrylate ester and (B) an anionic hydrophilizing agent. A method for producing a fibrous structure is also provided, which comprises a step of alkali treatment of a base fabric containing polyester fibers and cellulosic fibers, a step of applying (A') polyalkylene glycol diacrylate ester and (B) an anionic hydrophilizing agent, and a polymerization step, in this order.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a textile structure and a method for producing the textile structure. [Background technology]

[0002] Polyester fibers have excellent mechanical strength and chemical stability, are durable, can be washed under strong conditions, and dry quickly. Taking advantage of their ease of handling, textile structures made of polyester fibers are widely used as materials for everyday items such as clothing, bedding, and furniture.

[0003] However, polyester-based fibers made of hydrophobic resins have the disadvantage of being poorer in water absorption than polyamide-based fibers or cellulosic fibers, and when a textile product made of polyester-based fibers is used in a high-humidity environment or gets wet with water, the person using the textile product may feel stuffy or sticky.

[0004] Therefore, various attempts have been made to impart hydrophilicity to fiber structures made of polyester fibers.

[0005] For example, Patent Document 1 discloses a technique for modifying synthetic fibers using a diacrylic ester of polyoxyalkylene ether as a hydrophilizing agent.

[0006] Furthermore, Patent Document 2 describes a water-absorbing, quick-drying woven or knitted fabric composed of polyester fibers having a W-shaped, sheath-core structure with a specific flatness, in which a specific amount of polyethylene glycol is contained in the sheath of the polyester fibers and the polyester fibers are subjected to an alkali weight reduction treatment, thereby making the specific surface area of ​​the polyester fibers fall within a specific range.

[0007] In addition, fiber structures in which hydrophobic polyester fibers and hydrophilic cellulosic fibers are mixed or interwoven together are also widely used. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Japanese Patent Application Publication No. 52-150392 [Patent Document 2] JP 2008-150728 A Summary of the Invention [Problem to be solved by the invention]

[0009] In the polyester fiber structure obtained by the method of Patent Document 1, the moisture absorption can be improved more than that of an unprocessed fiber structure, but it is not sufficient. In addition, the polymerized hydrophilizing agent forms a three-dimensional network and adheres to the fiber surface, which causes an issue of hard texture.

[0010] The polyester fiber structure obtained by the method of Patent Document 2 uses yarn having a special composition and structure, and therefore has the problem of being unsuitable for general use and being expensive.

[0011] Furthermore, in fiber structures that simply combine polyester fibers and cellulosic fibers, there is an issue that the ease of removing dirt during washing (SR property) is reduced due to the properties of the cellulosic fibers.

[0012] Therefore, the present invention provides a fiber structure having excellent moisture absorption / release properties and SR properties and a soft feel, and a method for producing said fiber structure. [Means for solving the problem]

[0013] In order to solve the above problems, the fiber structure according to the present invention has the following configuration. (1) A fiber structure comprising a polyester fiber having a carboxy group in the molecular chain and a cellulosic fiber, and having (A) a polyalkylene glycol diacrylic ester polymer and (B) an anionic hydrophilic agent adhered to the fiber surface. (2) The fiber structure according to (1) above, wherein the (B) anionic hydrophilic agent includes at least one of a sulfonic acid-based hydrophilic agent and a sulfate-based hydrophilic agent. (3) The fiber structure according to (1) or (2), wherein the anionic hydrophilic agent (B) comprises: (B-1) a hydrophilic agent consisting of a polymer obtained by polymerizing a monomer capable of addition polymerization; and (B-2) a hydrophilic agent consisting of a compound not involved in addition polymerization. (4) The fiber structure according to any one of (1) to (3), having a tear strength of 4.0 N or more in both warp and weft directions as measured by method D (pendulum method) described in JIS L 1096:2020. (5) The fiber structure according to any one of (1) to (4), wherein the mass ratio of the polyester fibers to the cellulosic fibers is within a range of 85 / 15 to 33 / 67.

[0014] The method for producing a fiber structure according to the present invention has the following configuration. (6) A method for producing a fiber structure, comprising the steps of: subjecting a base fabric containing polyester-based fibers and cellulosic fibers to an alkali treatment; providing (A') a polyalkylene glycol diacrylic ester and (B) an anionic hydrophilic agent; and a polymerization step, in this order. Effect of the Invention

[0015] According to the present invention, it is possible to provide a fiber structure having excellent moisture absorption / release properties and SR properties and a soft feel, and a method for producing the fiber structure. [Brief description of the drawings]

[0016] [Figure 1] 1 shows 1000x scanning electron micrographs of the cross section of the base fabric used in Example 1, where (a) shows the state before the alkali treatment and (b) shows the state after the alkali treatment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, embodiments of the present invention will be described. Note that each of the embodiments described below shows a preferred specific example of the present invention. Therefore, the numerical values, shapes, materials, components, etc. shown in the following embodiments are merely examples and are not intended to limit the present invention. Therefore, among the components in the following embodiments, components that are not described in the independent claims showing the highest concept of the present invention will be described as optional components.

[0018] (Textile Structures) The fiber structure of the present invention is a fiber structure comprising a polyester fiber having a carboxy group in the molecular chain and a cellulosic fiber, and has (A) a polyalkylene glycol diacrylic ester polymer and (B) an anionic hydrophilic agent adhered to the fiber surface.

[0019] By combining hydrophilic cellulosic fibers with hydrophobic polyester fibers and attaching various hydrophilic agents (described below) to the fiber surfaces, the fiber structure is endowed with excellent moisture absorption and release properties resulting from an appropriate balance of hydrophilicity and hydrophobicity.

[0020] In addition, for cellulosic fibers that have low SR properties as they are, the SR properties can be improved by attaching a hydrophilic agent to the fiber surface. However, since the many hydroxyl groups in cellulose capture the growing species of addition polymerization, including radicals, and act as inhibitors, it is difficult to efficiently attach an addition-polymerizable hydrophilic agent to the surface of cellulosic fibers. Therefore, polyalkylene glycol diacrylic ester, which is an addition-polymerizable hydrophilic agent, is polymerized near the polyester fibers, and as a result, the polymer of polyalkylene glycol diacrylic ester is firmly fixed to the fiber surface in a form that involves the cellulose fibers. Furthermore, the anionic hydrophilic agent is also involved in the polymer of polyalkylene glycol diacrylic ester and fixed to the fiber surface, but the anionic hydrophilic agent is pushed out from the vicinity of the polyester fiber due to repulsion with the carboxy anion present in the polyester molecule, and is distributed in large amounts on the surface of the cellulosic fibers. Due to the above effects, a fiber structure with high SR properties can be obtained even if it contains cellulosic fibers with low SR properties.

[0021] The polyester fiber used in this embodiment is a polyester fiber having a carboxy group in the molecular chain. Specifically, the polyester resin is obtained by condensation polymerization of a dicarboxylic acid such as terephthalic acid or naphthalenedicarboxylic acid with a diol such as ethylene glycol, propylene glycol, or butylene glycol, or by condensation polymerization of a hydroxycarboxylic acid such as lactic acid, or by polyaddition involving ring opening of lactone, and the polyester resin is further hydrolyzed or modified with a carboxy group on the side chain, and the polyester resin is processed into a fiber shape. The carboxy group in the present invention includes a form in which the carboxy group is neutralized and exists as a salt or a carboxy anion, and most of them are negatively charged in the fiber structure treated with alkali. The presence of the carboxy group in the molecular chain can be confirmed by dyeing with a cationic dye.

[0022] The cellulose-based fiber used in the present embodiment is not particularly limited as long as it is a fiber made from cellulose. Specifically, the cellulose-based fiber may be at least one of natural fibers and regenerated fibers. The natural fiber may be at least one of cotton and hemp, and the regenerated fiber may be at least one of rayon, cupra, and polynosic. For natural fibers that tend to be hollow and flat, the cross-sectional shape of the fiber is corrected to a shape close to a circle by performing an alkali treatment described later, which also has the effect of improving the SR property, and therefore the effect is stronger when natural fibers are used.

[0023] The fiber structure of the present embodiment includes a polyester fiber having a carboxy group in the molecular chain and a cellulose fiber. The form in which the polyester fiber and the cellulose fiber are present is not particularly limited, and may be, for example, a fiber structure including a yarn in which the polyester fiber and the cellulose fiber are mixed or interwoven as a single yarn, or a fiber including the polyester fiber and a fiber including the cellulose fiber are interwoven or interknitted. In addition, the fiber structure may further include fibers of other materials within the scope of the present invention.

[0024] The ratio of the polyester fibers to the cellulose fibers is preferably within the range of 85 / 15 to 33 / 67 by mass ratio. If the ratio of the polyester fibers to the cellulose fibers is within the above range, it is preferable in that a moderate balance of hydrophilicity and hydrophobicity is exhibited, better SR properties are exhibited, and the strength and washability (resistance to shrinkage and wrinkles) of the fiber structure are easily ensured. A more preferable ratio is in the range of 80 / 20 to 40 / 60, and a particularly preferable ratio is in the range of 75 / 25 to 50 / 50. When performing alkali treatment, the polyester fibers may dissolve and become thin due to hydrolysis. In that case, the ratio of the polyester fibers to the cellulose fibers remaining after the alkali treatment may be adjusted to satisfy the above.

[0025] The fabric that is the base of the fiber structure of this embodiment is not particularly limited in its structure. Specifically, it may be a woven fabric with a structure such as plain weave, twill weave, or satin weave, a knitted fabric with plain stitch or tricot knitting, or a nonwoven fabric formed by a spunlace method or a needle punch method. Furthermore, it may be made into a pile fabric by knitting loop yarn, or may be flocked.

[0026] The fiber structure in this embodiment has (A) a polyalkylene glycol diacrylic ester polymer and (B) an anionic hydrophilic agent adhered to the fiber surface.

[0027] The (A) polyalkylene glycol diacrylic ester polymer refers to a polymer obtained by polymerizing the vinyl group of the (A') polyalkylene glycol diacrylic ester. The (A') polyalkylene glycol diacrylic ester refers to an ester compound of both terminal hydroxyl groups of a polyalkylene glycol and two molecules of acrylic acid or methacrylic acid. From the viewpoints of high hydrophilicity and economic efficiency, the polyalkylene glycol unit is preferably polyethylene glycol or polypropylene glycol, and the average degree of polymerization is preferably 9 or more, 15 or more, or 20 or more from the viewpoint of high hydrophilicity, and preferably 30 or less, 25 or less from the viewpoint of economic efficiency.

[0028] (B) Anionic hydrophilic agent refers to a compound having an anionic group in the molecular chain, specifically, a surfactant having at least one of a carboxy group, a sulfo group, a phosphoric acid ester, and a sulfate ester. From the viewpoint of a small acid dissociation constant and high hydrophilicity, it is preferable to include at least one of a sulfonic acid hydrophilic agent having a sulfo group and a sulfate ester hydrophilic agent containing a sulfate ester.

[0029] The anionic hydrophilic agent (B) may contain (B-1) a hydrophilic agent made of a polymer obtained by polymerizing a monomer capable of addition polymerization, and (B-2) a hydrophilic agent made of a compound not involved in addition polymerization. The hydrophilic agent (B-1) made of a polymer obtained by polymerizing a monomer capable of addition polymerization copolymerizes with (A') polyalkylene glycol diacrylic ester and remains in the vicinity of the polyester fiber, even though it is repelled by the carboxyl groups in the polyester molecule, and therefore exhibits a more remarkable effect of improving the SR properties of the polyester fiber.

[0030] (B-1) A hydrophilic agent consisting of a polymer obtained by polymerizing an addition-polymerizable monomer is a compound obtained by polymerizing (B-1') a compound having an addition-polymerizable multiple bond and an anionic functional group in the same molecule. Examples of the compound (B-1') include vinyl compounds and acrylic compounds having at least one of a carboxy group, a sulfo group, a phosphoric acid ester, and a sulfuric acid ester introduced therein, (meth)acrylic acid, crotonic acid, angelic acid, and tiglic acid.

[0031] (B-2) The hydrophilic agent made of a compound not involved in addition polymerization is an anionic surfactant that does not have addition-polymerizable multiple bonds. For example, the hydrophilic agent made of a compound not involved in addition polymerization can be selected from low molecular weight compounds that are at least one of alkylbenzene sulfonates such as sodium alkylbenzene sulfonate and alkyl sulfates such as sodium dodecyl sulfate, polymeric compounds in which at least one of a carboxy group, a sulfo group, a phosphoric acid ester, and a sulfuric acid ester is introduced into a resin such as a polyester resin, and combinations thereof. From the viewpoint of being unlikely to flow out into the washing liquid even after repeated washing, the hydrophilic agent made of a compound not involved in addition polymerization is preferably a polymeric compound in which at least one of a carboxy group, a sulfo group, a phosphoric acid ester, and a sulfuric acid ester is introduced into a resin such as a polyester resin.

[0032] The ratio of the amount of the hydrophilic agent (B-1) made of a polymer obtained by polymerizing a monomer capable of addition polymerization and the amount of the hydrophilic agent (B-2) made of a compound not involved in addition polymerization is preferably within a range of 90 / 10 to 65 / 35 by mass ratio. If it is within the above range, a fiber structure having a soft feel and high SR property is easily obtained.

[0033] The total mass of (A) the polyalkylene glycol diacrylic ester polymer and (B) the anionic hydrophilic agent attached to the fiber surface is preferably 2% to 15% of the total mass of the fiber structure. If it is 2% or more, a fiber structure with excellent moisture absorption and release properties and SR properties is easily obtained, and if it is 15% or less, a fiber structure with a soft texture is easily obtained. In addition, when a plurality of types of hydrophilic agents are used as anionic hydrophilic agents, for example, (B-1) a hydrophilic agent made of a polymer obtained by polymerizing a monomer capable of addition polymerization and (B-2) a hydrophilic agent made of a compound not involved in addition polymerization, the total mass is taken as the mass of (B) below.

[0034] The ratio of the amount of the polyalkylene glycol diacrylic ester polymer (A) to the amount of the anionic hydrophilic agent (B) attached is preferably within a range of 8 / 2 to 5 / 5, more preferably 7 / 3 to 6 / 4, in terms of mass ratio. Within this range, a fiber structure having high moisture absorption / release properties and high SR properties, which are expressed by the balance of hydrophobicity and hydrophilicity, can be easily obtained.

[0035] The fiber structure of the present embodiment may contain various functional agents within the scope of the present invention. Specifically, the fiber structure of the present embodiment may contain at least one of a polymerization initiator, a polymerization catalyst, a flame retardant, a hydrophilic agent different from the above, an ultraviolet absorbing agent, an infrared reflecting agent, a softener, a heat storage agent, a deodorizing agent, organic or inorganic particles for changing the feel, a coloring agent such as a dye or a pigment, and an antibacterial agent.

[0036] In particular, when an antibacterial agent is attached to the fiber surface, it can suppress the proliferation of bacteria on the surface of the fiber structure and suppress the generation of odors that become a problem when the fabric is wet due to sweat or half-dried when hung to dry indoors. In general, silver-based compounds are excellent antibacterial agents that have high antibacterial properties and a wide antibacterial spectrum even in very small amounts, but they tend to be washed away by washing and are therefore difficult to apply to fiber products that are washed frequently. However, with the fiber structure of this embodiment, the silver-based compounds can be firmly fixed to the fiber surface together with the hydrophilic agent, so that excellent antibacterial properties can be imparted to fiber products that are washed frequently.

[0037] Furthermore, the fiber structure of the present embodiment may be subjected to a process for changing the design thereof, specifically, a calendar process, a wrinkle process, a pleat process, a nap-raising process, a printed pattern, and the like.

[0038] The fiber structure of this embodiment may have a tear strength of 4.0 N or more in both warp and weft directions, measured by the D method (pendulum method) described in JIS L 1096:2020. If the tear strength is 4.0 N or more, the fiber product has mechanical strength and can suppress the occurrence of problems such as tearing and breaking during use. The polyester fiber of this embodiment is made of a polyester resin having a carboxy group in the molecule, but if the density of the carboxy group is too high, the tear strength tends to be weak. Therefore, the tear strength may be adjusted taking into account the composition of the fiber material constituting the base fabric, the thickness of the thread, the basis weight, the fiber density, etc., and the conditions of the reaction of the carboxy group to the polyester fiber. More preferably, the tear strength is 6.0 N or more in both warp and weft directions, and particularly preferably 7.0 N or more in both warp and weft directions. The upper limit of the tear strength is not particularly limited, but from the viewpoint of obtaining a fiber structure with a soft feel, it may be 70.0 N or less, 50.0 N or less, 30.0 N or less, 20.0 N or less, or 15.0 N or less. When the base fabric structure of the fiber structure is a knitted fabric, it is preferable that the above tear strength is satisfied in both the wale direction and the course direction. On the other hand, when the base fabric structure does not have anisotropy, such as in the case of a nonwoven fabric, the direction does not need to be taken into consideration.

[0039] (Method of manufacturing fiber structure) Next, a method for producing a fiber structure of the present invention will be described, with the contents overlapping with those described above being omitted as appropriate.

[0040] The method for producing a fiber structure of the present invention includes, in this order, a step of subjecting a base fabric containing polyester-based fibers and cellulosic fibers to an alkali treatment, a step of applying (A') a polyalkylene glycol diacrylic ester and (B) an anionic hydrophilic agent, and a polymerization step.

[0041] The method for producing a fiber structure in this embodiment uses a base fabric containing polyester fibers and cellulose fibers. As the polyester fibers, a polyester resin modified with a carboxyl group on the side chain may be used as the material, but from the viewpoint of the strength of the fiber structure and economic efficiency, it is preferable to use an unmodified general-purpose polyester resin as the material. For example, commonly available polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polylactic acid, etc. The composition of the cellulose fibers and the base fabric are as described above.

[0042] The method for producing a fiber structure in this embodiment includes a step of treating the base fabric with alkali (alkali treatment step). By treating the base fabric with alkali, the polyester resin constituting the polyester fiber is hydrolyzed to generate carboxyl groups and to soften the texture. When natural fibers are used as the cellulose fiber, the cross-sectional shape of the flat natural fiber can be corrected to a shape close to a circle, thereby improving the SR properties.

[0043] Specific conditions for the alkali treatment include immersing the base fabric in an alkaline aqueous solution containing 0.1% by mass to 5% by mass of sodium hydroxide or potassium hydroxide, and treating for 5 to 120 minutes at 65° C. to 135° C. The concentration, temperature and treatment time of the alkaline aqueous solution may be appropriately determined taking into consideration the texture and mechanical properties such as tear strength of the final fiber structure.

[0044] The alkali treatment can be carried out by immersing the base fabric in an alkaline aqueous solution, squeezing it with a mangle roll, etc., and then heat-treating it (padding treatment), but padding treatment can easily cause unevenness or streaks on the surface of the polyester fiber, which can lead to a decrease in SR properties and mechanical properties. Therefore, a method of treating the base fabric in an alkaline aqueous solution (bath treatment) is preferred. Specifically, the base fabric can be treated using a bath filled with an alkaline aqueous solution or a liquid flow dyeing machine.

[0045] Furthermore, if alkali remains in the base fabric after the alkali treatment, it can affect stability in subsequent processes and cause the unevenness of the fiber surface described above, so it is advisable to carry out an acid neutralization treatment or water washing treatment following the alkali treatment.

[0046] Furthermore, the polyester fiber may be subjected to a process for absorbing a flame retardant, a separate water absorbing agent, a disperse dye, etc., and the cellulose fiber may be dyed with a reactive dye. If these processes are performed after the hydrophilic agent providing process and the polymerization process described below, there is a risk that the hydrophilic agent will be removed from the fiber surface, so it is preferable to perform these processes after the alkali treatment process and before the hydrophilic agent providing process.

[0047] The method for producing a fiber structure in this embodiment includes, after the alkali treatment step, a step of applying (A') a polyalkylene glycol diacrylic ester and (B) an anionic hydrophilic agent (hydrophilic agent application step).

[0048] The method of applying the hydrophilic agent to the base fabric after the alkali treatment may be to apply an aqueous solution or aqueous dispersion (treatment liquid) containing the hydrophilic agent or an appropriate functional agent to the fabric by immersion, spraying, coating, etc. In order to remove excess treatment liquid from the base fabric, a process of squeezing with a mangle roll or blowing it off with an air blower may be added.

[0049] The concentrations of the (A') polyalkylene glycol diacrylic ester and the (B) anionic hydrophilic agent in the treatment solution may be appropriately set, taking into consideration the solids concentration of the agents and the pick-up rate onto the fabric, so that the agents are present in the above-mentioned ratio in the final fiber structure.

[0050] The functional agent may be any of those mentioned above, but it is advisable to add an appropriate polymerization initiator or polymerization catalyst in accordance with the polymerization mechanism of the polymerization step to be carried out subsequently.For example, when the hydrophilic agent is polymerized by radical polymerization, an initiator such as an inorganic initiator such as hydrogen peroxide or ammonium persulfate, an organic peroxide such as benzoyl peroxide or methyl ethyl ketone peroxide, an azo compound such as azobisisobutyronitrile, an aromatic ketone such as benzophenone, or a redox initiator combining an oxidizing agent and a reducing agent may be used in a dissolved or emulsified state in water.

[0051] In the method for producing a fiber structure in this embodiment, an anionic hydrophilic agent is used in the hydrophilic agent application step, so it is preferable not to use a cationic agent in the hydrophilic agent application step, which may electrically neutralize the anionic hydrophilic agent and cause gelation.

[0052] The method for producing a fiber structure in this embodiment includes, after the hydrophilic agent application step, a polymerization step for fixing the hydrophilic agent to the fiber surface.

[0053] The polymerization mechanism is not particularly limited as long as it is a mechanism that activates the addition-polymerizable multiple bonds contained in the molecules of the hydrophilic agent to cause a chain reaction of addition. For example, radical polymerization, cationic polymerization, anionic polymerization, coordination polymerization, etc. can be mentioned. Since cationic polymerization may cause gelation, and anionic polymerization and coordination polymerization make it difficult to control the deactivation of active species and catalysts, it is preferable to polymerize the hydrophilic agent by radical polymerization, which allows easy polymerization reaction.

[0054] The method of initiating and promoting polymerization may be appropriately set according to the selected polymerization mechanism. When polymerization is performed by radical reaction, the initiation and growth reaction may be promoted by applying dry heat or moist heat to the base material to which the hydrophilic agent has been applied, irradiating it with active energy rays such as ultraviolet rays or electron beams, or a combination of these. From the viewpoint of polymerization efficiency and processing stability, polymerization is preferably performed under moist heat conditions. As a specific moist heat processing condition, processing may be performed for 1 to 20 minutes in a chamber filled with steam at 80°C to 180°C or having a nozzle for spraying steam.

[0055] Furthermore, if any hydrophilic agent remains on the base fabric after the polymerization step, the final fiber structure may yellow or become brittle. Therefore, following the polymerization step, a washing treatment may be performed using water or a washing solution containing an appropriate surfactant.

[0056] Before or after each step, a heat setting step may be included for drying or adjusting the stiffness of the base fabric, if necessary. EXAMPLES

[0057] The present embodiment will be described in detail below with reference to examples, but the present invention is not limited to the following description. In the present invention, various physical properties were measured by the following methods.

[0058] (1) Confirmation of carboxyl groups (cationic dyeability) The test pieces were placed in a dye solution containing 0.01% omf KAYACRYL RED GL-ED (cationic dye, manufactured by Nippon Kayaku Co., Ltd.) and 2 g / L sodium acetate in an amount that gave a bath ratio (mass ratio) of 1:30, and dyed at 110°C for 30 minutes. Next, the test pieces were washed at 80°C for 30 seconds using a reducing solution containing 1 g / L sodium thiosulfate and 1 g / L sodium carbonate to wash off any unabsorbed dye. The test pieces were then dried, and the color intensity was determined using a staining gray scale conforming to JIS L 0805:2005. The lower the determined grade, the darker the test piece was dyed with the cationic dye, and it can be seen that the darker the test piece was dyed with the cationic dye, the more carboxyl groups there were in the test piece.

[0059] (2) Water absorption rate The measurement was carried out in accordance with the dropping method described in JIS L 1907:2010.

[0060] (3) Quick drying First, the test piece was left to stand in a chamber maintained under an environment of 20°C x 65% RH (relative humidity) for more than 4 hours to reach equilibrium. Next, the test piece was placed on a balance installed in the same chamber, and 0.3 g of water was dropped onto it, and the residual moisture content was calculated from the mass immediately after the dropping and 20 minutes later. It can be seen that the lower the residual moisture content, the faster the fiber structure dries.

[0061] (4) Moisture absorption and release properties The test piece was dried at 105°C for 24 hours, after which its mass was measured and designated as the bone dry mass W0. The test piece was then left to stand in an environment of 20°C and 65% RH for 24 hours, after which its mass was measured and designated as W1. The test piece was then left to stand in an environment of 30°C and 90% RH for 24 hours, after which its mass was measured and designated as W2. From these, the moisture absorption and release properties were calculated using the following formulas 1, 2, and 3, and the average of the measured values ​​for the four samples (n=4) was designated as the moisture absorption and release value. It can be seen that the higher the moisture absorption and release value, the higher the moisture absorption and release property of the fiber structure. AL(%)=(W1-W0) / W0×100...(Formula 1) AH(%)=(W2-W0) / W0×100 (Equation 2) Moisture absorption and release (%) = AH-AL (Formula 3)

[0062] (5)SR A polyethylene sheet was laid on a glass plate (7.5cm x 15cm x 0.15cm), a test piece of 15cm x 15cm was placed on the polyethylene sheet, and one drop of diamond paste liquid was dropped on the test piece. Next, a polyethylene sheet was placed on the test piece and the diamond paste, and a glass plate (7.5cm x 15cm x 0.15cm) was placed on it, and a 2kg weight was placed on it for 30 seconds. Next, the polyethylene sheet was removed, and the test piece was sandwiched between filter paper instead, and a 2kg weight was placed on it again for 30 seconds, and then the test piece was removed and left to stand for 3 hours. The test piece prepared by the above method was washed three times by the C4M method described in JIS L 1930:2014 Appendix F and dried. After that, the degree of contamination of the test piece by the diamond paste was judged using the above-mentioned gray scale for contamination. The diamond paste was prepared by diluting 1 g of a mixture of 16.7% by mass of carbon black, 20.8% by mass of hardened beef tallow oil, and 62.5% by mass of liquid paraffin with 100 ml of motor oil (engine oil for automobiles). It can be seen that the higher the determined series, the higher the SR property of the test piece.

[0063] (6) Tear strength The measurements were taken four times in each of the warp and weft directions, and the average values ​​were calculated, using a method conforming to the D method (pendulum method) described in JIS L 1096: 2020. For example, the "9.9 x 7.4" for the tear strength (N) in Example 1 in Table 1 indicates that the average value in the warp direction is 9.9 N and the average value in the weft direction is 7.4 N, and the same applies to other Examples and Comparative Examples.

[0064] (7) Texture Test pieces measuring 25 cm x 25 cm were cut out, and the texture when rubbed with hands was evaluated according to the following criteria. ◎: Very soft ○: Soft ×: The core is felt and is hard

[0065] (Example 1, Comparative Example 1) <Base fabric> First, general-purpose polyethylene terephthalate / cotton blend yarns with a mass ratio of 65 / 35 and a fineness of 50 dtex were plain woven for both the warp and weft to obtain a plain woven fabric with a weave density of 110 threads / 2.54 cm x 76 threads / 2.54 cm.

[0066] <Alkaline treatment process> The base fabric was subjected to an alkali treatment using a liquid jet dyeing machine under the conditions of a bath ratio of 1:20 and 130°C for 30 minutes using an aqueous solution containing 1.0% sodium hydroxide. Next, the fabric was rinsed with warm water at 70°C and then dried to obtain an alkali-treated base fabric. The alkali-treated base fabric had a fabric weight reduction of 28.2% from before the alkali treatment, and the blend ratio of the alkali-treated base fabric was polyester / cotton = 51 / 49 by mass. In addition, when a cationic dyeability test was performed on the alkali-treated base fabric, it was dyed with a concentration of grade 4, and it was confirmed that a carboxyl group was generated in the molecular chain of the polyester fiber. In addition, the base fabric at this stage was used as a comparative example (Comparative Example 1) in which the hydrophilic agent application process and the polymerization process were omitted, and various performances are listed in Table 1.

[0067] Figure 1 is a 1000x cross-sectional photograph of the base fabric used in Example 1 taken by a scanning electron microscope, where Figure 1(a) shows the state before the alkali treatment, and Figure 1(b) shows the state after the alkali treatment. Referring to Figure 1(a), it can be seen that before the alkali treatment, the base fabric is a blend of polyethylene terephthalate fibers that are solid and have a cross section that is nearly circular, and hollow, flat cotton fibers. On the other hand, referring to Figure 1(b), it can be seen that the cotton fibers have become somewhat plump from their flat state by the alkali treatment, as shown by the arrows, and some cotton fibers have been corrected to a shape closer to a circle.

[0068] <Hydrophilic Agent Application Step> Next, a treatment solution having the composition shown below was applied to the alkali-treated base fabric by padding.

[0069] (A'): Polyethylene glycol dimethacrylate (average degree of polymerization of ethylene glycol units: 23)...2.00 mass% (B-1'): Sodium styrenesulfonate 1.00% by mass (B-2): Sulfonic acid-modified saturated polyester resin: 0.17 mass% (Anionic radical polymerization initiator): Ammonium persulfate: 0.10% by mass (Dispersion medium): Water...Remainder

[0070] <Polymerization process> The fabric was then treated in a normal pressure steamer at 115° C. for 7 minutes. It was then rinsed with warm water at 80° C., dried, and further finished and set at 160° C. to obtain a fiber structure. The various properties of the obtained fiber structure are shown in Table 1.

[0071] (Examples 2 to 3, Comparative Examples 2 to 3) A fiber structure was obtained in the same manner as in Example 1, except that the composition of the treatment liquid used in the hydrophilic agent application step was changed to the concentration shown in Table 1. Various properties of the obtained fiber structure are shown in Table 1.

[0072] Comparative Example 4 For the base fabric, general-purpose polyethylene terephthalate / cotton blend yarns with a mass ratio of 50 / 50 and a fineness of 50 dtex were plain woven for both the warp and weft to obtain a plain weave fabric with a weave density of 110 threads / 2.54 cm x 76 threads / 2.54 cm.

[0073] A fiber structure was obtained in the same manner as in Example 1, except that the alkali treatment step was omitted for the base fabric. Various properties of the obtained fiber structure are shown in Table 1.

[0074] [Table 1]

[0075] Referring to Table 1, it can be seen that in the fiber structure of Comparative Example 1, the hydrophilic agent application step and the polymerization step were omitted, so that the (A) polyalkylene glycol diacrylic ester polymer and the (B) anionic hydrophilic agent were not attached to the fiber surface, and the SR property was poor. In addition, because these were not attached to the fiber surface, the effect of improving moisture absorption and release based on a suitable balance of hydrophobicity and hydrophilicity could not be obtained. In the fiber structure of Comparative Example 2, the SR property was somewhat improved compared to the fiber structure of Comparative Example 1 by including the (A) polyalkylene glycol diacrylic ester polymer, but since the fiber structure did not include the (B) anionic hydrophilic agent, the effect of improving SR property was insufficient, and the effect of improving moisture absorption and release based on a suitable balance of hydrophobicity and hydrophilicity could not be obtained sufficiently. Similarly, in the fiber structure of Comparative Example 3, the SR property was somewhat improved compared to the fiber structure of Comparative Example 1 by including the anionic hydrophilic agent (B). However, since the fiber structure did not include the polyalkylene glycol diacrylic ester polymer (A), the improvement effect of the SR property was insufficient, and the improvement effect of the moisture absorption and release property based on the balance of the appropriate hydrophobicity and hydrophilicity could not be obtained sufficiently. In the fiber structure of Comparative Example 4, the alkali treatment step was omitted, so that a sufficient texture was not obtained. At the same time, the result of the cationic dyeability test was grade 5 or higher, and a carboxyl group could not be generated in the molecular chain of the polyester fiber. Therefore, the improvement effect of the SR property was insufficient, even though the polyalkylene glycol diacrylic ester polymer (A) and the anionic hydrophilic agent (B) were used.

[0076] In contrast, the fiber structures of Examples 1 to 3 contain polyester fibers having carboxy groups in the molecular chain and cellulosic fibers, and (A) a polyalkylene glycol diacrylic ester polymer and (B) anionic hydrophilic agent are attached to the fiber surfaces. In other words, by attaching a specific hydrophilic agent to the fiber surfaces of the fiber structures containing hydrophobic polyester fibers and hydrophilic cellulosic fibers, excellent moisture absorption and release properties are achieved due to an appropriate balance of hydrophilicity and hydrophobicity, and higher SR properties and a soft texture can be obtained.

Claims

1. A fiber structure comprising a polyester fiber having a carboxy group in its molecular chain and a cellulosic fiber, and having (A) a polyalkylene glycol diacrylic ester polymer and (B) an anionic hydrophilic agent adhered to the surface of the fiber.

2. The fiber structure according to claim 1 , wherein the anionic hydrophilic agent (B) includes at least one of a sulfonic acid-based hydrophilic agent and a sulfate-based hydrophilic agent.

3. The fiber structure according to claim 1 or 2, wherein the anionic hydrophilic agent (B) comprises: (B-1) a hydrophilic agent composed of a polymer obtained by polymerizing a monomer capable of addition polymerization; and (B-2) a hydrophilic agent composed of a compound not involved in addition polymerization.

4. The fiber structure according to claim 1 or 2, wherein the tear strength measured by the D method (pendulum method) described in JIS L 1096:2020 is 4.0 N or more in both warp and weft directions.

5. The fiber structure according to claim 1 or 2, wherein the mass ratio of the polyester fiber to the cellulosic fiber is within a range of 85 / 15 to 33 / 67.

6. A method for producing a fiber structure, comprising the steps of: subjecting a base fabric containing polyester-based fibers and cellulosic fibers to an alkali treatment; applying (A') a polyalkylene glycol diacrylic ester and (B) an anionic hydrophilic agent; and a polymerization step, in that order.

Citation Information

Patent Citations

  • Hydrophilic agent

    JP1977150392A

  • Water-absorbing / quick-drying woven and knitted fabrics

    JP2008150728A